If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(8h + 7) = 34 Reorder the terms: -5(7 + 8h) = 34 (7 * -5 + 8h * -5) = 34 (-35 + -40h) = 34 Solving -35 + -40h = 34 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + -40h = 34 + 35 Combine like terms: -35 + 35 = 0 0 + -40h = 34 + 35 -40h = 34 + 35 Combine like terms: 34 + 35 = 69 -40h = 69 Divide each side by '-40'. h = -1.725 Simplifying h = -1.725
| X-(-7)=56 | | x^2-(3+6i)x-18+2i=0 | | 5x+3(x+7)=-(2x+5) | | 5y+1+3b=2 | | (x-y+3z)(x-y-7z)= | | (z+5)(z-2)=-5 | | 3x+x+2=2x+4 | | 3(2x+1)=2x+15 | | 4(x-1)-3(x-2)+2(x+1)=10 | | 17+b=-3 | | -3x*(9x32)/2 | | 12-(-3x+2)=25 | | (a-2b+1)(a-2b+5)= | | 10+3z=19 | | 1x+59+84+1x+51=180 | | 1/2n=5/18*3/5 | | (a+b+3)(a+b+4)= | | 2v+7=29 | | x^2-3x+6ix-18+2i=0 | | T/8-1=2 | | 1=m-15 | | 2w+4x+13y+8w+7x-4y= | | 3x-(7+x)=-23 | | (x-10)(x-2)= | | 4=24-54 | | -20=-20x | | 7d+15=92 | | X^2+3x+2y-7=0 | | (m+7)(m-4)= | | x+(4x+3)=-7 | | 1.2=x^21 | | -88=-8(a+4) |